Артроподофауна фондосховища Одеського музею західного і східного мистецтва - Коритнянська, В.Г. (Сіверщина в історії України, 2023)
У статті наведені результати вивчення артроподофауни фондосховища Одеського музею західного і східного мистецтва. У результаті ентомологічних обстежень 2018−2022 рр. У приміщеннях фондів закладу виявлено членистоногих − представників чотирьох класів (Вищі раки, Губоногі, Комахи та Павукоподібні), з них найбільш чисельними за кількістю таксономічних груп були класи Комахи та Павукоподібні. Серед виявлених артропод зареєстровані музейні шкідники (шість видів) та організми-індикатори незадовільного санітарно-гігієнічного стану музейних приміщень, їх недостатньої ізоляції від навколишнього середовища, наявності в них зон мікроклімату та ін. As a result of entomological studies conducted during 2018−2022, the species composition of the arthropods of the museum stores of Odesa Museum of Western and Eastern Art was established. The identified arthropods belonged to four classes (Malacostraca, Chilopoda, Insects, and Arachnids), of them the most numerous in terms of the number of taxonomic groups were classes Insects (representatives of 7 orders were registered, 7 species were identified) and Arachnids (2/1). Among the discovered representatives of the phylum Arthropoda, six species belonged to the group of museum pests, however, according to observations, in the museum stores were development only of carpet beetles (Dermestidae: Anthrenus spр. and Attagenus spр., during the entire period of observations, in deposits of dust and dirt) and biscuit beetles (Ptinidae, Stegobium paniceum (Linnaeus, 1758), in certain years, probably outside the artworks). Episodic and few finds of other pests, in particular, moths, Silverfish, booklice, wood-boring weevils, probably indicate their periodic («accidental») appearance in the museum stores. In general, despite the rather significant variety of species of pests found in the museum’s stores, cases of damage by them of museum objects in institution during the entire period of observations were not registered. At the same time, the annual findings in the halls of the museum stores (in the vast majority of specimens) of woodlice, species of the order Hemiptera (from families Rhyparochromidae, Coreidae, Pentatomidae, etc.), ants and spiders testify to the unsatisfactory sanitary and hygienic condition of the premises of the museum stores and their poor proofing from the environment, episodic detection of plaster beetles, booklice, sciariids, oribatid mites and mycetophagous mites − about the presence of microclimate zones indoor of museum stores, which are characterized by high moisture content (not lasting) and, probably, the development of microscopic fungi in them.